Canakinumab as first-line biological therapy in Still’s disease and differences between the systemic and the chronic-articular courses: Real-life experience from the international AIDA registry - Vitale, Antonio; Caggiano, Valeria; Maggio, Maria Cristina; Lopalco, Giuseppe; Emmi, Giacomo; Sota, Jurgen; La Torre, Francesco; Ruscitti, Piero; Bartoloni, Elena; Conti, Giovanni; Fabiani, Claudia; Mattioli, Irene; et al. (Frontiers in Medicine, 2022)
Objective: the current therapeutic approach tends to prefer the use of interleukin (IL)-1 inhibitors in patients with the systemic type of Still’s disease, while IL-6 inhibitors are more frequently employed in patients with the chronic-articular form of Still’s disease. The aim of the present study is to assess any difference in the effectiveness of the IL-1β antagonist canakinumab prescribed as first-line biologic agent between the systemic and the chronic-articular Still’s disease. Methods: data were drawn from the retrospective phase of the AutoInflammatory Disease Alliance (AIDA) international registry dedicated to Still’s disease. Patients with Still’s disease classified according to internationally accepted criteria (Yamaguchi criteria and/or Fautrel criteria) and treated with canakinumab as first-line biologic agent were enrolled. Results: 26 patients (17 females, 9 males; 18 patients developing Still’s disease after the age of 16 years) were enrolled; sixteen (61.5%) patients suffered from the systemic pattern of the disease; 10 (38.5%) patients suffered from the chronic-articular type. No differences were observed between the systemic and the chronic-articular Still’s disease in the frequency of complete response, of flares after the start of canakinumab (p=0.701) and in the persistence in therapy (p=0.62). No statistical differences were observed between the two groups after 3 months, 12 months and at the last assessment in the decrease of: the systemic activity score (p=0.06, p=0.17, p=0.17, respectively); the disease activity score on 28 joints (p=0.54, p=0.77, p=0.98, respectively); the glucocorticoid dosage (p=0.15, p=0.50 and p=0.50, respectively); the use of concomitant disease modifying anti-rheumatic drugs (p=0.10, p=1.00 and p=1.00, respectively). No statistically significant differences were observed in the decrease of erythrocyte sedimentation rate (p=0.34), C reactive protein (p=0.48), and serum ferritin levels (p=0.34) after the start of canakinumab. Conclusions: canakinumab used for Still’s disease has proved to be effective in controlling both clinical and laboratory manifestations disregarding the type of disease course when used as first-line biotechnological agent. These excellent results might have been further enhanced by the early start of IL-1 inhibition